Thermal Study of a Newly Synthesized Cu(II) Complex Binding to Bovine β-Lactoglobulin - Adeleh Divsalar; Lyla Barzegar; Gholamreza Rezaei Behbehani (Journal of Chemistry)
We have investigated the interactions between β-lactoglobulin, BLG, and new synthesized Cu(II) complex (2,2′-dibipyridine Cu(II) chloride) using isothermal titration calorimetry (ITC) methods at different temperatures of 298 and 310 K. The heats of BLG + Cu(II) interactions are reported and analyzed in terms of the extended solvation theory for calculation of binding and thermodynamic parameters of the interaction. The results suggested that binding of Cu(II) complex on BLG resulted in significant changes on the tertiary structure and conformation of protein via increasing of hydrophobicity and inducing partially unfolded structure in BLG which has a good agreement with the solvation parameters recovered by the extended solvation model suggesting destabilization of the protein.